Sulfation of a FLAG tag mediated by SLC35B2 and TPST2 affects antibody recognition. - Xin-Yu Guo; Xiao-Dong Gao; Morihisa Fujita (PLoS ONE)
A FLAG tag consisting of DYKDDDDK is an epitope tag that is frequently and widely used to detect recombinant proteins of interest. In this study, we performed a CRISPR-based genetic screening to identify factors involved in the detection of a FLAG-tagged misfolded model protein at the cell surface. In the screening, SLC35B2, which encodes 3'-phosphoadenosine-5'-phosphosulfate transporter 1, was identified as the candidate gene. The detection of FLAG-tagged misfolded proteins at the cell surface was significantly increased in SLC35B2-knockout cells. Furthermore, protein tyrosine sulfation mediated by tyrosyl-protein sulfotransferase 2 (TPST2) suppressed FLAG-tagged protein detection. Localization analysis of the FLAG-tagged misfolded proteins confirmed that defects in tyrosine sulfation are only responsible for enhancing anti-FLAG staining on the plasma membrane but not inducing the localization change of misfolded proteins on the plasma membrane. These results suggest that a FLAG tag on the misfolded protein would be sulfated, causing a reduced detection by the M2 anti-FLAG antibody. Attention should be required when quantifying the FLAG-tagged proteins in the secretory pathway.